2018
DOI: 10.1667/rr14987.1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in C3H Mice Protected from Lethal Total-Body Radiation after Amifostine

Abstract: Amifostine is a potent antioxidant that protects against ionizing radiation effects. In this study, we evaluated the effect of Amifostine administered before total-body irradiation (TBI), at a drug dose that protects against TBI lethality, for potential protection against radiation-induced late effects such as a shortened lifespan and cancer. Three groups of mice were studied: 0 Gy control; 10.8 Gy TBI with Amifostine pretreatment; and 5.4 Gy TBI alone. Animals were monitored for their entire lifespan. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Amifostine is an antioxidant and radioprotector that works by scavenging hydroxyl radicals (HO • ) [135]. In a phase III clinical trial of squamous head and neck cancer patients, amifostine was found to have protective effects on acute and delayed xerostomia but not severe oral mucositis [136] and has been studied broadly in clinical trials with RT with or without concurrent chemotherapy [137].…”
Section: Amifostinementioning
confidence: 99%
“…Amifostine is an antioxidant and radioprotector that works by scavenging hydroxyl radicals (HO • ) [135]. In a phase III clinical trial of squamous head and neck cancer patients, amifostine was found to have protective effects on acute and delayed xerostomia but not severe oral mucositis [136] and has been studied broadly in clinical trials with RT with or without concurrent chemotherapy [137].…”
Section: Amifostinementioning
confidence: 99%
“…The irradiation exposure was performed by using X-Ray 225 (Radsource, North Branford, CT, USA) with exposure dose rate of 219.93 cGy/min. According to the literature [ 10 ], the total irradiation dose was 30 Gy and the irradiated area was 2 cm×5 cm and 5 mm lead was used.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopy, mucosal biopsy and esophageal barium film were used to test the pathological changes and evaluate the efficacy of drugs [17]. The changes of body weight, survival time, esophageal pathology and inflammatory cell score have also been used to evaluate the efficacy of the drug in the treatment of radiation induced esophagitis in C3H mice [10].…”
Section: Lack Of Objective Criteria or Tools Is A Hurdle To Evaluate mentioning
confidence: 99%
“…post-exposure growth factors and cytokines) (Seed et al 2014;Hofer et al 2017;Singh and Seed 2019). Amifostine treatment also protected against radiation-induced hematopoietic tumors, while protection against solid neoplasms was significant but incomplete (Cook et al 2018).…”
Section: Aminothiolsmentioning
confidence: 99%